Nutritional status and eating habits of the institutionalised elderly in Turkey: a follow‐up study. Issue 2 (3rd June 2015) - Rakıcıoğlu, N.; Aksoy, B.; Tamer, F.; Yıldız, E. Akal; Samur, G.; Pekcan, G.; Besler, H. T.
Abstract: Background: As the elderly population increases in Turkey, so do the associated health and nutritional problems. The main purpose of the present study was to determine the nutritional status of elderly individuals who live in institutions. Methods: A total of 102 elderly volunteers was recruited from seven residential homes of the Ministry of Family and Social Policies in Ankara. In the consecutive years of 2007, 2008 and 2009, dietary intake was assessed using a 24‐h food recall. Nutritional status was screened using a questionnaire from the Mini‐Nutritional Assessment, basic characteristics were determined and anthropometric measurements were assessed. Results: The percentage of elderly participants who were malnourished or at risk for malnutrition increased by the completion of the follow‐up ( P < 0.05). It was found that energy, total protein, animal proteins, carbohydrates, niacin, vitamin C, vitamin E and zinc intake of men decreased significantly over the years studied ( P < 0.05). A significant decrease occurred among women in animal protein, vitamin B1, niacin and the percentage of energy from proteins ( P < 0.05); however, an increase in energy from fat ( P < 0.05) was determined. Within the years studied, the percentage of nutrients meeting the Turkish recommended daily allowances decreased from 2007 to 2009 both in men and women. During the years 2007 to 2009, the percentage of waist circumferences >102 cm for men was 46.4%, 45.6% and 48.1%, respectively, and the percentage of waist circumferences for women >88 cm was 75.6%, 75.6% and 81.8%, respectively. Conclusions: During the follow‐up, significant nutritional changes were determined. To prevent malnutrition, periodical screening of nutritional status should be a priority and a standard policy for elderly people, especially for those institutionalised.